2007
DOI: 10.1590/s1516-44462006005000061
|View full text |Cite
|
Sign up to set email alerts
|

Weight gain, dyslipidemia and altered parameters for metabolic syndrome on first episode psychotic patients after six-month follow-up

Abstract: Clinicians should be aware of these risks, choose an antipsychotic that causes less weight gain and should monitor these patients carefully, and recommend prophylactic measures as diet restriction and physical activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 24 publications
(16 reference statements)
5
14
3
Order By: Relevance
“…Our data on metabolic changes were in alignment with recent prospective studies in first-episode patents (Attux et al, 2007;Perez-Iglesias et al, 2008;Saddichha et al, 2007;Srisurapanont et al, 2007) and confirmed the differences between SGA in their liability to induce metabolic changes (Cohn and Sernyak, 2006;L'Italien et al, 2007;Newcomer, 2005;van Winkel et al, 2008).…”
Section: Discussionsupporting
confidence: 90%
“…Our data on metabolic changes were in alignment with recent prospective studies in first-episode patents (Attux et al, 2007;Perez-Iglesias et al, 2008;Saddichha et al, 2007;Srisurapanont et al, 2007) and confirmed the differences between SGA in their liability to induce metabolic changes (Cohn and Sernyak, 2006;L'Italien et al, 2007;Newcomer, 2005;van Winkel et al, 2008).…”
Section: Discussionsupporting
confidence: 90%
“…Hypotheses on the association between schizophrenia and diabetes (adapted from Leucht et al [2007aLeucht et al [ , 2007b of the study group varied, however male patients appeared to be over represented. In most studies the mean age of participants in the study group was over 40 years of age, and only a few studies referred to patients with first episode schizophrenia [Attux et al 2007;Saddichha et al 2007;De Hert et al 2008b;Saddichha et al 2008;Curtis et al 2011]. The predominant diagnosis of patients studied was schizophrenia, however a great number of studies also included patients with schizoaffective disorder and other psychotic disorders.…”
Section: Study Selectionmentioning
confidence: 99%
“…Incidence of metabolic syndrome A minority of studies calculated incidence rates of MetS [Attux et al 2007;L'Italien et al 2007;Saddichha et al 2007;Srisurapanont et al 2007;De Hert et al 2008b;Meyer et al 2008;Kim et al 2010;Kraemer et al 2010]. The results were hardly comparable in this field as incidence rates were calculated for various time periods, from 6 weeks up to 1 year.…”
Section: Metabolic Syndrome and Lifestyle Habitsmentioning
confidence: 99%
“…Some recent studies have also emphasized the relevance of the problem in Brazil, particularly in psychotic disorders 33,34 . Teixeira and Rocha 12 , applying NCEP-ATP III criteria, found elevated rates of MS in psychiatric inpatients with schizophrenia (40%) BD (42.9%) and major depressive disorder (52.9%).…”
Section: Discussionmentioning
confidence: 99%